The Victorian Illustrating of Shakespeare’s Women: Metal Engraving - Afrooz Khaleghi; Morteza Lak; Hoda Shabrang (زن در فرهنگ و هنر)
This article seeks to examine the illustrated editions of Shakespeare's plays, whose images were printed by the use of metal engraving, in order to find the most determining factors that affect the way of understanding the female characters in the play, and to answer the question, "What is the Victorian portrayal of women’s main features in Shakespeare's editions?" Since advanced types of engraving such as steel engraving, outline engraving, stipple, daguerreotype and photogravure were among the main techniques for reproducing images in the Victorian period, representing Shakespeare's women as aesthetic paratexts of 19th century printed editions was an artistic selection which added a layer of non-textual appeal to the plays and enhanced the reading quality and hermeneutic understanding of the characters. In other words, artists and editors sought to emphasise their beauty, strength, and complexity by depicting Shakespeare's heroines in visually appealing ways. Therefore, the illustrations in these editions provided the readers with a richer interpretation of the characters and potentially influenced their understanding of the characters in the play. Moreover, in this era, the images went from emphasising the conceptual and semantic connection of the images of women with the text, which was common in the eighteenth century, to simply representing the beauty of women. It is worth mentioning that to fully describe this process, William John Thomas Mitchell's ideas about the importance of visual presentation of literary texts will be relied upon.